Extended radical cholecystectomy with curative potential for well selected locally advanced carcinoma gall bladder: a case report and review of literature - Thammaiah, Pradeep (International Surgery Journal, 2022)
Gallbladder cancer is an aggressive malignancy that is associated with a poor prognosis. While surgical resection provides the only curative option, the majority of patients are not considered resectable due to locally advanced disease and presence of metastatic disease at the time of presentation. Here we presented a case of 46-year-old female with symptoms and initial workup suggestive of obstructive jaundice with cholestasis. PET-CT demonstrated heterogeneously enhancing mass lesion arising from neck of gallbladder and involving adjacent liver parenchyma with FDG avid para-aortic nodes. Liver biopsy confirmed adenocarcinoma, ERCP revealed tight hilar structure and CBD stent was placed. Patient was diagnosed with cT4, N2 carcinoma gall bladder and received two cycles of neoadjuvant chemotherapy (NACT) with gemcitabine and cisplatin. In view of localized and stable disease following NACT, patient underwent radical cholecystectomy with wide liver resection involving segment 4b and 5 with hepatoduodenal, portocaval and aortocaval lymph node dissection. Patient had post-operative complications, managed conservatively. On follow up patient had improved appetite, gained weight adequately, received adjuvant chemotherapy and is disease free till date. Carefully selected patients may benefit from an aggressive surgical approach following upfront systemic chemotherapy.